Rare birds in Nepal - Inskipp, Carol; Baral, Hem Sagar; Acharya, Sanjib; Chaudhary, Hathan; Ghimire, Manshanta; Giri, Dinesh (Nepalese Journal of Zoology, 2020)
This paper aimed to fulfil the knowledge gap on the status of vagrants and rare birds of Nepal. Records of all Nepal’s bird species that were previously considered vagrants by the National Red List of Nepal’s Birds (2016) were collated and detailed with localities, dates and observers. Species recorded since 2016, including vagrant species, were also covered. A total of 92 species was assessed to determine if they were vagrants, that is species that had a total of 10 or less records. It was concluded that six species are no longer vagrant and we recommend these for national red list assessment. Nepal currently has a total of 71 vagrant species. In addition, four vagrant species have still to be accepted by the Nepal Rare Birds Committee before they can be officially included on the Nepal bird list. Nine species have so far only been recorded in the 19th century. Red-faced liocichla Liocichla phoenicea, was previously one of these, but was re-found In Nepal after the National Red List was published in 2016; it is a very rare and very local resident. Himalayan grasshopper-warbler Locustella kashmirensis is a recent split and now considered a full species (instead of a subspecies); it is probably an altitudinal migrant in Nepal. Despite great advances in our ornithological knowledge of Nepal, there is still high potential to find new species, especially of passerine birds and in the less explored parts of the country.